INTEGRATION OF AQUACROPS, AGRICULTURE AND DAIRY FARMING IN A DERELICT WETLAND OF NORTH BIHAR - Verma, Anand Mohan (Journal of the Inland Fisheries Society of India, 2016)
INTEGRATION OF AQUACROPS, AGRICULTURE AND DAIRY FARMING IN A DERELICT WETLAND OF NORTH BIHAR